A systematic review of the literature on affective tutoring systems: 2001-2020 - Castillo Avila, Arlem Aleida (2021)
The interest in the development of intelligent tutoring systems has generated a wide range of multidisciplinary research studies, as well as the development of tools for different applications. Among them are those tutors that integrate the affective state of the student when having an interactive session. A systematic review of the literature on emotion-aware intelligent tutoring systems, called affective tutoring systems, was conducted between 2001 and 2020. This paper reports the results of a bibliometric analysis to a set of 198 papers obtained from the Web of Science, Scopus, ERIC and Dimensions. The main findings are reported in relation to 7 research questions, 3 of which involved a qualitative analysis, and finally some preliminary conclusions are given, considering the situation of Mexico regarding the development of affective tutoring systems.